2018
DOI: 10.1097/hco.0000000000000476
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter device closure of atrial septal defects

Abstract: As TC-ASD and congenital interventional cardiology mature as a field, studies of real-world practice provide increasingly valuable information about aspects of care in which there are disagreements about best practices and in which further research is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Transthoracic and transcatheter device closures of ASDs have been increasingly reported in recent years; the previous reports also confirmed that there were low morbidity and mortality in both treatments [ 5 , 6 ] . With the accumulation of experience and the progression of technology, these two treatments have tended to replace surgical repair for the treatment of ASDs [ 10 ] . Transcatheter device closure of ASDs has the advantages of no incision and a short hospitalization time [ 11 , 12 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Transthoracic and transcatheter device closures of ASDs have been increasingly reported in recent years; the previous reports also confirmed that there were low morbidity and mortality in both treatments [ 5 , 6 ] . With the accumulation of experience and the progression of technology, these two treatments have tended to replace surgical repair for the treatment of ASDs [ 10 ] . Transcatheter device closure of ASDs has the advantages of no incision and a short hospitalization time [ 11 , 12 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Since proven effective, transthoracic echocardiography (TTE)-guided percutaneous ASD closure (the PAN procedure) has been performed in an increasing numbers of patients [ 2 – 4 ] avoiding exposure to radiation and use of lead suit protection [ 5 ]. However, mastering the PAN procedure requires getting used to guidance by echocardiographic plane-by-plane scanning instead of fluoroscopic 3D image projections onto a 2D plane which facilitates finding the guide wire tip [ 4 , 6 ]. To overcome the latter learning curve limitation and the fact that available guide wires were designed for fluoroscopic and not for echocardiographic guidance, we designed a novel guide wire with a spindle tip, specialized for ultrasound guidance.…”
Section: Introductionmentioning
confidence: 99%